Aspects on Fundaments and Applications of Conducting Polymers - de Jesus Motheo, Artur (IntechOpen, 2012)
Since the establishment of the conductive properties of intrinsic conductive polymers, a huge variety of basic and applied research has been carried out, involving different polymers, copolymers, blends, mixtures and composites. Thus, fundamental understanding of physical and chemical properties of these materials has been sought, while the applied aspects have advanced very rapidly, crossing the boundaries between disciplines. Today, the applications of conducting polymers in various fields such as neuroscience, nanotechnology and green chemistry, are easily found. This development is dynamic and it needs to be updated and hence the motivation for the set of results presented in this book; which provides information about the development of fundamentals, and about some applications of conductive polymers.